2003
DOI: 10.1046/j.1365-2141.2003.04349.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities in childhood acute myeloid leukaemia: a Nordic series comprising all children enrolled in the NOPHO‐93‐AML trial between 1993 and 2001

Abstract: Summary. Between 1993 and 2001, 318 children were diagnosed with acute myeloid leukaemia (AML) in the Nordic countries. The patient group comprised 237 children < 15 years of age with de novo AML, 42 children < 15 years with Down syndrome (DS) and de novo AML, 18 adolescents 15-18 years of age with de novo AML, and 21 children < 15 years with treatment-related AML (t-AML). The first group was all-inclusive, yielding an annual childhood de novo AML incidence of 0AE7/100 000. Cytogenetic analyses were successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 42 publications
7
54
2
2
Order By: Relevance
“…Future global gene expression analyses should be able to clarify whether there are significant differences in expression patterns of CEBP gene family members between DS-ALL and non-DS-ALL. Regarding AML, and in line with several previous studies, 4,29,34,38,39 the present compilation clearly revealed that t(8;21), 11q23 translocations, and inv(16) are significantly less common in DS-AML than in non-DS-AML (Table 2). Furthermore, none of the 136 DS-AMKL harbored the t(1;22), verifying that this translocation is very rare indeed in this AML type.…”
Section: Org Fromsupporting
confidence: 80%
See 2 more Smart Citations
“…Future global gene expression analyses should be able to clarify whether there are significant differences in expression patterns of CEBP gene family members between DS-ALL and non-DS-ALL. Regarding AML, and in line with several previous studies, 4,29,34,38,39 the present compilation clearly revealed that t(8;21), 11q23 translocations, and inv(16) are significantly less common in DS-AML than in non-DS-AML (Table 2). Furthermore, none of the 136 DS-AMKL harbored the t(1;22), verifying that this translocation is very rare indeed in this AML type.…”
Section: Org Fromsupporting
confidence: 80%
“…Not surprisingly, frequent gain of this chromosome has been found in most previous studies of DS-AML. 4,10,15,29,38,[40][41][42][43][45][46][47] Less well appreciated is the fact that ϩ8 often is the sole acquired anomaly in DS-AML, being found in 30% of the cases with single anomalies. Thus, this abnormality is undoubtedly intimately involved in the leukemogenesis of DS-AML.…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…A cute leukemia is the most common malignancy in childhood, with an incidence of 4 and 0.7 cases of acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML), respectively, per 100,000 children per year (1,2). The outcome for children with ALL and AML has improved significantly over the last two decades, with the overall event-free survival approaching 80% and 50%, respectively (1,3).…”
mentioning
confidence: 99%
“…Three (trisomy) or four (tetrasomy) copies of chromosome 21 is common in childhood acute lymphoblastic leukemia (ALL) [2][3][4]. Children with Down syndrome (DS) who carry trisomy 21 in all their cells have a 20-fold increased risk for childhood ALL and 600-fold risk for acute megakaryocytic leukemia (AMKL) [5].…”
Section: Aneuploidy Of Chromosome 21 and Acute Megakaryocytic Leukemiamentioning
confidence: 99%